Literature Review: Strategi Guru dalam Menggunakan Aplikasi Artificial Intelligence di Indonesia - Latifah, Rizka (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Artificial Intelligence (AI) involves developing computer systems capable of human-like intelligence, including the ability to think, experience emotions, and adapt to new situations. The increasing prevalence of AI in education has led to significant changes in schools, particularly in the learning process. This article explores the use of Artificial Intelligence in Indonesian education through a literature review. We used a systematic literature review with the PRISMA diagram for article selection. The data analysis technique used is thematic analysis. The analysis focused on the applications of AI, the perspectives of teachers and students, and strategies teachers can implement to integrate AI into learning. This study identified four teacher strategies for implementing AI in education: enhancing teacher competency, integrating AI with appropriate learning methods, preserving the crucial role of human interaction, and establishing guidelines for AI usage.